139 Establishment of canine CAR T cells treatment model for solid tumor immunotherapy development. (9th November 2020) - Zhang, Shihong; Kohli, Karan; Graeme Black, R; Hayes, Brian; Miller, Cassandra; Maeda-Whitaker, Mari; Schroeder, Brett; Abrams, Kraig; Seguin, Bernard; Gottschalk, Stephen; Moore, Peter; Torok-Storb, Beverly; et al.
Abstract : Background: Chimeric antigen receptor (CAR) T cell therapy has transformed therapy for hematological malignancies but has not yet been established as standard of care for any solid tumors. One obstacle for human solid tumor immunotherapy research is the lack of clinically relevant, immunocompetent animal models. In this study, we sought to establish CAR T cells for naturally occurring canine sarcomas in client owned animals as a model for human CAR T cell therapy. Methods: Archived FFPE, freshly isolated canine solid tumor samples as well as tumor lines were tested for B7H3 expression by immunohistochemistry (IHC) and flow cytometry analysis. We designed CARs using the scFv from the human B7H3-specific antibody MGA271 and confirmed the cross-reactivity to canine B7H3 (construct information see figure 1 A). A truncated EGFR (tEGFR) was included in the construct to allow for IHC and flow cytometry testing for the presence of CAR T cells. Killing efficiency was evaluated using 3D tumor spheroid killing assays to monitor dynamics. Safety of the CAR products following lymphodepletion was confirmed in two healthy dogs (figure 1 B). Results: Canine solid tumors were confirmed to be B7H3 positive in almost all cases. Using the GALV-pseudotyped retrovirus system, transduction was efficient with up to 70% CAR+ cells. Post-transduction expansion was over 100 folds. B7H3 CAR transduced canine T cells were able to eliminate B7H3+ canine tumor spheroids effectively (figure 2 ). Safety of the CAR T cells (dose: 1 × 10 9 /m 2 ) were confirmed in both healthy animals following cyclophosphamide lymphodepletion. After week 6, cetuximab was given to the subjects to deplete EGFR+ cells. Subject 2 experienced fever after CAR T cell administration. Both dogs showed elevated serum ALP and ALT levels and returned to normal (figure 3 ). No other treatment-related adverse events were observed. Information of the CAR T cell products can be found in table 1 . Conclusions: We demonstrated that, similar to human cancers, B7H3 is a target in canine solid tumors. We successfully generated canine B7H3 specific CAR T cell products that are highly efficient at killing canine 3D tumor spheroids using a production protocol that closely models human CAR T cell production procedure and confirmed the safety in vivo. We plan to test and optimize various approaches to enhance CAR T cell efficacy for solid tumor treatment both in vitro and in canine sarcoma patients. Ethics Approval: The study was approved by Fred Hutchinson Cancer Research Center's Institutional Animal Care and Use Committee (IACUC), approval number PROTO201900860